On the onset of breathing mode in Hall thrusters and the role of electron mobility fluctuations - Leporini , L.; Giannetti , V.; Saravia , M. M.; Califano , F.; Camarri, S.; Andreussi , T. (Frontiers in Physics, 2022)
Breathing mode is an ionization instability which is observed ubiquitously in the operation of Hall thrusters. It is recognized as a relatively low frequency (10-30kHz), high amplitude, longitudinal oscillation of the discharge current and the plasma parameters. Although breathing instability is widely studied in the literature, the conditions for its origin are not fully understood. In this work we investigate the mechanisms responsible for the origin of the breathing mode in Hall thrusters by using a numerical model, allowing us to highlight the importance of electron mobility fluctuations for the onset and self-sustenance of the instability. Our one-dimensional, fully fluid model of the thruster channel is calibrated against the measured discharge current signal for a 5kW-class Hall thruster operating in a condition where breathing mode is fully developed. The corresponding steady, unstable configuration (base state) is numerically computed by applying the Selective Frequency Damping (SFD) method. Then, a series of numerical tests is performed to show the existence of a feedback loop involving fluctuations around the base state of the neutral density, electron mobility and electric field. We show that oscillations of the electron mobility are mainly caused by variations of the neutral density and are in phase with them; this, in turn, induces oscillations of the electric field, which are in phase opposition. The electric field acts simultaneously on the electron temperature and on the ion dynamics, promoting the filling and replenishment of neutrals in the chamber.